2005
DOI: 10.2169/internalmedicine.44.1064
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Graves' Disease Accompanied by Bloody Pericardial Effusion

Abstract: A hyperthyroid patient with bloody pericardial effusion is presented. He was hospitalized for severe dyspnea. Pericardiocentesis yielded 1.2 liters of bloody fluid. Biochemical, cytologic, and radiologic examinations failed to identify the etiology of the effusion. Upon normalization of thyroid function using antithyroid drugs, the pericardial effusion resolved without recurrence. The patient was diagnosed as Graves' disease, which rarely is complicated by bloody pericardial effusion. As it is rarely reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…In fact, positive TSH-R Abs highly suggest Graves' disease in a thyrotoxic patient even if it is subclinical [3,6]. Additionally, there are also case reports in English literature regarding development of pericardial effusion in patients with Graves' disease [7,8]. As a conclusion, the diagnosis of Hashitoxicosis in this patient is questionable and the definitive diagnosis would be possible in the follow-up period, in which transient thyrotoxicosis followed by hypothyroidism would strongly suggest Hashitoxicosis while sustained hyperthyroidism would favor Graves' disease.…”
Section: Dear Editormentioning
confidence: 99%
“…In fact, positive TSH-R Abs highly suggest Graves' disease in a thyrotoxic patient even if it is subclinical [3,6]. Additionally, there are also case reports in English literature regarding development of pericardial effusion in patients with Graves' disease [7,8]. As a conclusion, the diagnosis of Hashitoxicosis in this patient is questionable and the definitive diagnosis would be possible in the follow-up period, in which transient thyrotoxicosis followed by hypothyroidism would strongly suggest Hashitoxicosis while sustained hyperthyroidism would favor Graves' disease.…”
Section: Dear Editormentioning
confidence: 99%
“…The mechanism for the development of a pericardial effusion with Graves' disease has not been elucidated. Previous authors have postulated that the mechanism is similar to that of the ophthalmopathy and myxedema found in hyperthyroidism [ 2 , 5 , 8 ]. A study of hypothyroidism found shifts in extravascular and intravascular proteins and a decrease in lymph drainage [ 10 ].…”
Section: Discussionmentioning
confidence: 90%
“…Contrastingly, in our review of the literature, we found only 10 previously reported cases of pericardial effusion in the setting of hyperthyroidism ( Table 1 ). Four of the pericardial effusions were sanguineous [ 2 , 5 , 7 , 8 ]. Similar to our patient, six of the patients had Graves' disease [ 2 , 3 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are many cases of pericardial and pleural effusion in the setting of hypothyroidism but only very few case reports in the literature which have described association of pleural and pericardial effusions with Graves' hyperthyroidism (6,7).…”
Section: Discussionmentioning
confidence: 99%